Do CSR and GCG have an Impact on ROE? - Nieke Ayu Pramudita; Wirawan Endro Dwi Radianto (Enrichment : Journal of Management, 2023)
The overarching goal of the present research is to examine the influence of CSR and GCG as proxied by the board of commissioners, independent commissioners, and audit committee on ROE with company size as a control variable. Purposive sampling was utilized in the sampling process and between 2017 and 2022, this study identified 27 companies from the energy and basic materials sectors registered on the Indonesia Stock Exchange, forming a representative sample. The outcomes from this study indicates that there are no significant impact of CSR on ROE. On the other hand, independent commissioners negatively influence ROE, while the board of commissioners as well as audit committee have a positive impact. The presence of company size as a control variable in this research also influences the company's ROE